An investigation on laser/DP-MIG hybrid weldability of aluminum to Al-Si coated boron steel. (June 2022) - Cao, Xiaobing; Duan, Ji'an; Li, Zhou; Chang, Baoqi; Xu, Cong; Xie, Zheng
Highlights: A novel laser/DP-MIG hybrid welding-brazing was developed to join aluminum to Al-Si coated boron steel. Maintaining an appropriate heat input in a low level was necessary for a satisfactory IMC thickness and appearance. The phases of τ5 -Fe2 Al8 Si, θ-Fe(Al, Si)3 and η-Fe2 (Al, Si)5 were nicely confirmed in detail. The variation of failure modes and their fracture mechanism were analyzed. Abstract: Laser/double pulse-MIG (laser/DP-MIG) hybrid welding-brazing of 5052 aluminum alloy to Al-Si coated boron steel was successfully conducted in a lap configuration with an Al-5Si filler. The heat input plays a significant role in determining the welding performance. The satisfactory appearance and excellent brazed interface with a maximum thickness of 4.1 μm was achieved at the optimum heat input of 161.8 J/mm, and the maximum joint strength reached to 168.8 MPa in excess of 75% aluminum resistance. Three kinds of intermetallic compounds (IMC) phases were nicely identified: τ5 -Fe2 Al8 Si, θ-Fe(Al, Si)3 and η-Fe2 (Al, Si)5 . Microstructure evolution of brazed joint showed that microstructure of upper-critical HAZ (UCHAZ) consisted of martensite whereas that of inter-critical HAZ (ICHAZ) consisted of ferrite and martensite. The two failure modes (interfacial failure (IF) and HAZ failure (HF)) was associated with the interfacial characteristic and porosity percentage. IF mode was a typical intergranular fracture, and its cracks initiated from notch of weld joint and then redirected toward the region of pore concentration. HF mode was a mixture of major ductile fracture and minor cleavage fracture, and its cracks might initiate from notch of weld joint and then propagated along the IMC throughout the whole interface.